EFFECTS OF VARIOUS FUNGICIDES AGAINST CORYNESPORA CASSIICOLA IN VITRO - P. MOUNIKA,; S. L. BHATTIPROLU, (The Journal of Research ANGRAU, 2024)
In order to determine the efficacy of eleven fungicides against Corynespora cassiicola causing Corynespora leaf spot of cotton, an experiment was carried out during 2012-22 employing poisoned food technique. The results of radial growth and inhibition of growth over control revealed that variation existed in the sensitivity of C.cassiicola towards different test fungicides. Among the six straight fungicides, carbendazim @ 0.1% and hexaconazole @ 0.2% amended medium promoted zero growth i.e., complete inhibition of C. cassiicola. In propiconazole @ 0.1% amended medium, the growth was 0.9 cm equivalent to 89.7% inhibition. Among the five combination fungicides,fluxapyroxad + pyraclostrobin @ 0.06% and metiram + pyraclostrobin @ 0.3% gave 100% inhibition.